Night shift : a novel - Cook, Robin, 1940- (New York : G. P. Putnam's Sons, 2022)
"In this exhilarating medical mystery-thriller by Robin Cook, fan favorites Jack and Laurie are lured into the dark underbelly of hospital dangers when an internist is murdered"--
Publishers Weekly
Kirkus Reviews
Library Journal Prepub Alert
Keywords: Murder -- Investigation -- Fiction; Private investigators -- Fiction; Forensic pathologists -- Fiction; Detective and mystery stories; Mystery fiction